Coordination Models and Languages 14th International Conference, COORDINATION 2012, Stockholm, Sweden, June 14-15, 2012. Proceedings - Sirjani, Marjan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 14th International Conference on Coordination Models and Languages, COORDINATION 2012, held in Stockholm, Sweden, in June 2012, as one of the DisCoTec 2012 events. The 18 revised full papers presented were carefully reviewed and selected from 55 submissions. The papers cover a wide range of topics including coordination of social collaboration processes, coordination of mobile systems in peer-to-peer and ad-hoc networks, programming and reasoning about distributed and concurrent software, types, contracts, synchronization, coordination patterns, and families of distributed systems.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer Science; Software Engineering; Programming Techniques; Software Engineering/Programming and Operating Systems; Computer Communication Networks; Models and Principles; Information Systems Applications (incl. Internet).